2003
DOI: 10.1128/jb.185.9.2739-2748.2003
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Surface Proteins ofErysipelothrix rhusiopathiaeBind to Polystyrene, Fibronectin, and Type I and IV Collagens

Abstract: Erysipelothrix rhusiopathiae is a gram-positive bacterium that causes erysipelas in animals and erysipeloid in humans. We found two adhesive surface proteins of E. rhusiopathiae and determined the nucleotide sequences of the genes, which were colocalized and designated rspA and rspB. The two genes were present in all of the serovars of E. rhusiopathiae strains examined. The deduced RspA and RspB proteins contain the C-terminal anchoring motif, LPXTG, which is preceded by repeats of consensus amino acid sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 61 publications
(77 reference statements)
0
66
0
2
Order By: Relevance
“…Protein repeat motifs have been identified in many virulence-related proteins of gram-positive bacteria, where they have been found to function as ligands to various host receptors or to have specific affinity for cellular components (36,41). Although the role of the Afp13 repeat structure has yet to be elucidated, it is not believed to be a virulence factor by itself.…”
Section: Discussionmentioning
confidence: 99%
“…Protein repeat motifs have been identified in many virulence-related proteins of gram-positive bacteria, where they have been found to function as ligands to various host receptors or to have specific affinity for cellular components (36,41). Although the role of the Afp13 repeat structure has yet to be elucidated, it is not believed to be a virulence factor by itself.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fact that CCL5 has two BBXB motifs that bind to GAGs (30) but fail to bind Col IV indicates that electrostatic interactions alone are not sufficient for chemokines to bind Col IV. Given that Col IV can interact with a variety of structurally different proteins, including ECM components (31,32), growth factors (33,34), proteinases (35,36), and bacterial proteins (37,38), multiple mechanisms are probably used to bind these molecules. Detailed structural analyses will be needed to understand the precise mechanisms underlying the selective binding by Col IV of lymphoid chemokines.…”
Section: Discussionmentioning
confidence: 99%
“…Although no function of the Sca proteins was demonstrated, it was suggested that some autotransporters have adhesion or protease activities and could play a role in rickettsial virulence (38,69). A characteristic of bacterial adhesins that bind to eukaryotic extracellular matrix proteins is the presence of amino acid repeats (57). A 50-residue repeat occurs six times within the carboxy-terminal portion of the Sca2 passenger domain, suggesting that this protein may be involved in binding of R. typhi to host cells.…”
Section: Vol 186 2004mentioning
confidence: 99%